Leadership and Job Stress among Non-Civil Servants: Job Satisfaction Mediation and Employment Status Moderation - Darmadi Darmadi; Desi Prasetiyani; Guruh Dwi Pratama; Suwanto Suwanto (Goodwood Publishing, 2026)
Purpose: This study examines the effect of leadership on job stress among non–civil servant government employees, including Government Employees under Work Agreements (PPPK), by analyzing the mediating role of job satisfaction and the moderating role of employment status. Research Methodology: A quantitative survey was conducted among non–civil servant and PPPK employees in the South Tangerang City Government. From a population of 3,327 employees, 357 respondents were selected using proportional random sampling methods. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine the direct, mediating, and moderating effects. Employment status was treated as a categorical moderator distinguishing PPPK employees from other contract-based staff members. Results: Leadership had a significant negative effect on job stress (? = ?0.380, p < 0.001) and a significant positive effect on job satisfaction (? = 0.519, p < 0.001). Job satisfaction significantly reduced job stress (? = ?0.433, p < 0.001) and partially mediated the relationship between leadership and job stress (? = ?0.225, p < 0.001). Employment status significantly moderated the relationship between job satisfaction and job stress (? = ?0.086, p = 0.024). Conclusions: Job stress among non–civil servant public employees is influenced by leadership quality, job satisfaction, and employment status. Limitations: The cross-sectional design and single local government context limit the generalizability of the findings. Contributions: This study contributes to the public-sector human resource management literature by integrating leadership, job satisfaction, and employment status within a mediation–moderation framework based on the Job Demands–resources perspective.